2p-4f MOFs based on naphthalene-1, 4, 5, 8-tetracarboxylate with magnetocaloric effect and slow magnetic relaxation properties. (16th August 2017) - Zhang, Shi-Yong; Liang, Fu-Yong; Wen, He-Rui; Liu, Sui-Jun; Lu, Xiao-Neng; Du, Zi-Yi
Graphical abstract: Three new three-dimensional Na–Ln MOFs have been constructed via hydrothermal reaction, and complex1 displays a large magnetocaloric effect with −Δ S m max = 28.8 J kg −1 K −1 and complex2 show field-induced slow magnetic relaxation behaviors. Abstract: A family of new three-dimensional (3D) 2 p -4 f metal-organic frameworks (MOFs), namely [Na2 Ln(L)(OH)(H2 O)3 ] n (H4 L = naphthalene-1, 4, 5, 8-tetracarboxylic acid, Ln = Gd (1 ), Tb (2 ) and Dy (3 )) have been synthesized by using hydrothermal method and structurally characterized by single-crystal X-ray diffraction, powder X-ray diffraction and IR spectra. Complexes1 –3 are isostructural and crystallize in the space group Cmca of orthorhombic system. Their crystal structures can be described as a kind of homeomorphism configurations with 3D framework. Magnetic measurements indicated that complex1 exhibits antiferromagnetic behavior and magnetocaloric effect with −Δ S m max = 28.8 J kg −1 K −1 (Δ H = 7 T and T = 2 K), and complex2 exhibits field-induced slow magnetic relaxation behaviors.